A comparison between the welcoming system and the diameter of the nodhi projector, an analytical study - عبدول, د. سه ربه ست نادر; Mustafa, Dr. Mohamed Ahmed (Sulaimani Journal for Humanities, 2026)
This study aims to make a comprehensive comparison between the welcoming system and the projector diameter of the nudhi in the context of the study of the science of obligations. The study will focus on analyzing the methodology used in each of the two systems, and the similarities and differences between them will be established. The study will also include an introduction indicating the importance of this comparison in the context of the study of the science of obligations, and will present the research objective which includes the comparison between my system of al-Rahbiyah and Qatar al-Aradh of al-Nawdhi in terms of the methodology used by Imam al-Rahbi and Shaykh al-Nawdhi. The similarities and differences between these two systems will be analyzed in the context of the study of the science of duties.
Keywords: Comparison; system; alRahbi; Qatar viewer; alNodhi